Distance learning technologies at the postgraduate stage of professional development of pharmacists - M. O. Avramenko; N. O. Tkachenko; Yu. Yu. Riabokon; O. A. Bigdan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
Today, pharmaceutical education has to respond flexibly, dynamically and adequately to social transformations by developing new educational services, teaching technologies and organizing the training process. In response to the demand of the time, postgraduate professional education strives to meet the current needs; a new concept of increasing the effectiveness of education and the professional level of specialists has been formed: lifelong learning is impossible without the use of information and communication technologies.